2020
DOI: 10.1038/s41598-020-62581-z
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and anti-inflammatory potential of Angelica dahurica and Rheum officinale extract accelerates wound healing in Staphylococcus aureus-infected wounds

Abstract: Wound infection is a serious clinical problem, and the most common infection-causing bacteria are Staphylococcus aureus and Pseudomonas aeruginosa. Angelica dahurica and Rheum officinale extract (ARE) was reported to accelerate excisional wound healing in rats. In this study, we investigated the therapeutic effects of ARE on bacterial-infected wounds. Thirty Sprague-Dawley rats were divided into three groups: normal saline (NS), ARE, and biomycin ointment (BO). Full-thickness dorsal excisions in all the rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Following A. dahurica treatment, the secretion of inflammatory factors, such as IL-1β, TNF-α, and IL-6 also reduced significantly, which is of great significance to diminish wound inflammatory cell infiltration. This finding is consistent with previous studies that indicated A. dahurica decreased inflammatory cytokines levels, such as TNF-α, IL-6, and accelerated wound closure in rats ( Yang et al, 2020 ). Furthermore, a recent study reported that A. dahurica decreased the mRNA expression of IL-6, IL-4, and TNF-α in the tissues of mice skin.…”
Section: Discussionsupporting
confidence: 93%
“…Following A. dahurica treatment, the secretion of inflammatory factors, such as IL-1β, TNF-α, and IL-6 also reduced significantly, which is of great significance to diminish wound inflammatory cell infiltration. This finding is consistent with previous studies that indicated A. dahurica decreased inflammatory cytokines levels, such as TNF-α, IL-6, and accelerated wound closure in rats ( Yang et al, 2020 ). Furthermore, a recent study reported that A. dahurica decreased the mRNA expression of IL-6, IL-4, and TNF-α in the tissues of mice skin.…”
Section: Discussionsupporting
confidence: 93%
“…Most published research on rhubarb has been conducted using organic extract of the roots. Organic extract of Rheum officinale was shown to have strong activity against S. aureus [ 33 ]. Emodin, an anthraquinone in the organic extract, can block the SARS coronavirus spike protein and angiotensin-converting enzyme 2 interaction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 ]. Several previous studies have also reported that the roots of A. dahurica exhibit various pharmacological functions, including antibacterial, anti-asthmatic, hypotensive, anti-inflammatory, antioxidation, anti-cancer, and anti-Alzheimer effects [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Pharmacological functions of A. dahurica are generally attributed to coumarins (oxypeucedanin, bergapten, imperatorin, cnidilin, isoimperatorin, xanthotoxol, oxypeucedanin hydrate, byakangelicin, etc.…”
Section: Introductionmentioning
confidence: 99%